2016
DOI: 10.1002/lno.10331
|View full text |Cite
|
Sign up to set email alerts
|

Recent accelerated warming of the Laurentian Great Lakes: Physical drivers

Abstract: The primary drivers of the recent accelerated warming of the Laurentian Great Lakes from 1982 to 2012 are explored through observations, remote sensing, and regional climate model experiments. The study focuses on the abrupt warming from 1997 to 1998 as a proxy for the long‐term warming trend. The lake surface warming has been heterogeneous in both space and time, ranging from moderate warming in late spring over the southern lakes and shallow areas of the northern lakes to strong warming in mid‐summer over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(132 citation statements)
references
References 70 publications
11
120
0
1
Order By: Relevance
“…This would allow one to directly simulate fundamental lake‐climate interactions, thus improving the simulation of both lake processes and regional climate. Recent attempts in this direction have been made to adopt one‐dimensional lake models (e.g., Goyette and Perroud, ; Zhong et al ; Sugiyama et al ), which however require an entire set of meteorological variables, causing a potentially larger propagation of uncertainties and errors typical of climate models. An example is given by the comparison between air2water (Piccolroaz et al ) and a coupled RCM‐lake model (Zhong et al ) for the case of Lake Superior (U.S.A.‐Canada), where the latter model is characterized by larger errors, with many cases being statistical significant.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow one to directly simulate fundamental lake‐climate interactions, thus improving the simulation of both lake processes and regional climate. Recent attempts in this direction have been made to adopt one‐dimensional lake models (e.g., Goyette and Perroud, ; Zhong et al ; Sugiyama et al ), which however require an entire set of meteorological variables, causing a potentially larger propagation of uncertainties and errors typical of climate models. An example is given by the comparison between air2water (Piccolroaz et al ) and a coupled RCM‐lake model (Zhong et al ) for the case of Lake Superior (U.S.A.‐Canada), where the latter model is characterized by larger errors, with many cases being statistical significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, LSWT warming rates may be more consistent with air temperature rates depending on future stabilization in air quality improvements [4,39]. Similarly, milder winters, shortening ice cover and less snow cover on ice occurring in NENA and around the northern latitudes [50,51] will all contribute to lowered lake albedo, earlier stratification and longer duration of energy absorption, resulting in intensified summer warming [11,12,52]. Changes in wind speed [53,54], water transparency [55,56] and hydrologic inflows [54] can all alter lake warming rates.…”
Section: Near-surface Warmingmentioning
confidence: 99%
“…However, a direct cause and effect relationship of winter ice cover on summer LSWTs has yet to be reported, and its influence in driving excess summer LSWT warming is in question 21 . Moreover, other studies have demonstrated that ice cover is not a prerequisite for accelerated summer LSWT warming 12, 22 .…”
Section: Introductionmentioning
confidence: 99%